AGU Journals Are Compliant With Research Councils UK Open Access Policies. (2nd April 2013) - Hanson, Brooks
Abstract : The Research Councils UK (RCUK) has mandated that after 1 April 2013, papers with RCUK funding be submitted to journals that are compliant with its open‐access policy. This policy requires "immediate and unrestricted access to the final published version of papers" and use of the Creative Commons Attribution License (known as CC‐BY). Copyright remains with the authors.